Microwave-assisted Synthesis of Some Benzimidazole Derivatives: A Case for a Comparative Study - Mobinikhaledi, A.; Forughifar, N.; Amrollahi, M. (Asian Journal of Chemistry, 2016)
Benzimidazole derivatives (3a-k) were synthesized in high yield (80-95%) using a microwave assisted cyclocondensation reaction of o-phenylenediamine and a carboxylic and a carboxylic acid under acidic medium. Products were recrystallized from a mixture of ethanol and water. Synthesis of benzimidazole derivatives under microwave irradiation is found much easier and faster than conventional heating method.